Frontline Health Care Workers' (HCWs) perception of barriers to managing COVID-19 in Fiji - Deo, Anjana; Mohammadnezhad, Masoud (Frontiers in Public Health, 2022)
Background: Health Care Workers (HCWs) are at higher risk of coronavirus disease 19 (COVID-19) infection their efforts while protecting the greater community and also exposed to hazards such as psychological distress, fatigue and stigma. This study aimed to explore the perception of frontline HCWs on barriers of managing COVID-19 in Fiji. Methods: A qualitative study method was approached to conduct this study among, HCWs Central division of Fiji in 2020. This study was conducted at the ten purposively selected health facilities in Suva sub division. HCWs who work as frontline in COVID-19 in ten health facilities at Central division were chosen based on the study criteria. A semi- structured open ended questionnaire was used to collect data using in- depth interviews. The participants’ responses were audio- recorded and were later transcribed and analyzed using the thematic analysis. Results: Twenty-nine HCWs took part in the in-depth interview and the responses were grouped into four themes. They include; workload, communication, resources, and hindrance to education. It was also found through this study that some of the HCWs felt tiring, hard, frustrating, gets rude to patients, find it difficult to handle the situation, affected mentally, physically and stressed. Conclusion: While managing the COVID-19 cases has been attributed to the presence of many barriers such as workload, feel tiring, frustrated and sometimes difficult to handle the situation while the HCWs gets affected mentally and physically as well. More awareness programs would help the general public to follow the preventive measures, which reduces the cases and would help the HCWs managing the COVID-19 well.